Evaluasi User Experience Gim Mobile Legends: Bang Bang menggunakan Design Thinking - Evika Septianawati; Ismiarta` Aknuranda; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Mobile Legends: Bang Bang (MLBB) is one of the most popular online games in Indonesia. However, based on preliminary research that has been conducted online through a questionnaire, there are several factors that users do not like when playing the Mobile Legends game. Often players who play in rank mode solo (without playing together), are made into trouble by some players who have unpleasant behavior, one example of which is toxic players. This continues until the current Mobile Legends season. The purpose of this study is to explore the factors that users do not like when playing the Mobile Legends game and propose solution ideas that can support and solve problems experienced by players. This study uses Design Thinking, every action taken using this process is centered on what the user wants and needs. There are several stages in Design Thinking, namely Empathize, Define, Ideate, Prototype, and Test. At the Empathize stage, 7 problems were found, then the information that had been collected during the Empathize stage through interviews was analyzed and synthesized in the Define stage and produced 5 problem statements. At the Ideate stage, 5 solution ideas were generated, the solution ideas were implemented at the prototype stage and tested using the Feedback Capture Matrix to get user feedback.